The Economics of Disequilibrium Price - Robinson, Romney (Quarterly Journal of Economics, 1961)
I. Introduction, 199. — II. Market-determined and code-established prices, 201. — III. The market-determined price in pure oligopoly, 202. — IV. The code-established price in pure oligopoly, 205. — V. Price discrimination, 208. — VI. Differentiated oligopoly, 210. — VII. The demand curve as an analytic concept, 212. — VIII. Code-established prices in pure competition, 215. — IX. The indeterminacy of purely market-determined pricing, 218. — X. Monopolistic conspiracy versus cutthroat competition, 220. — XI. The shapes of demand and cost curves, 222. — XII. Excess capacity, 226. — XIII. The structure of the code-established price, 228. — XIV. Behavior codes, 230. — XV. Conclusion, 232.